Divergent Enantioselective Total Synthesis of Siphonarienal, Siphonarienone, and Pectinatone. Issue 10 (16th October 2013) - Yadav, Jhillu Singh; Chary, D. Narasimha; Yadav, Nagendra Nath; Sengupta, Sandip; Subba Reddy, Basi V.
Abstract A divergent synthesis of siphonarienal, siphonarienone, and pectinatone has been achieved from a common precursor 4, which was synthesized by using an enzymatic desymmetrization approach. The major key steps involved were Grignard reaction, Wittig reaction, Evans' asymmetric alkylation, and base‐catalyzed cyclization.